Strategi Guru Menciptakan Kelas yang Kondusif untuk Membangun Keaktifan Siswa di MA Hidayatul Islamiyah Plumpang - Muhammad Amaruddin Asy Syarif; Siti Khalima; Emi Nur Sa’diyah (Moral : Jurnal kajian Pendidikan Islam, 2025)
Conducive classroom conditions are an important factor in increasing student activity in the learning process, especially in Madrasah Aliyah (MA). Teachers have an important and strategic role in creating a learning environment that supports active student participation. This study aims to analyze the strategies implemented by teachers in building a conducive classroom and its impact on student activity. The method used in this study is a qualitative method with data collection techniques through observation, interviews, and documentation. The results of this study indicate that effective strategies include the application of an interactive learning approach, the use of varied learning media, the creation of a comfortable classroom atmosphere, and providing motivation and appreciation to students. By implementing these strategies, teachers can increase student involvement in learning, increase interaction between students and teachers, and build a pleasant and productive learning atmosphere. In conclusion, the application of the right strategy by teachers contributes significantly to creating a conducive classroom and increasing student activity at MA Hidayatul Islamiyah.